2023
DOI: 10.1021/acs.analchem.3c01008
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of An Aptamer-Functionalized Fluorescent DNA Sensor for Cu(II) Responding in Living Tumor Cells

Abstract: Copper ions play vital roles in regulating life processes and being closely involved in several diseases such as cancer. Although detection methods based on fluorescent sensors or other strategies have been developed, it still remains a challenge to simultaneously realize the convenience, specificity, and accuracy in intracellular copper ion analysis. Herein, we propose an aptamer-functionalized DNA fluorescent sensor (AFDS) for accurate and specific detection of Cu(II) both in vitro and in cells by engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Meanwhile, the inconspicuous G4 topology could be detected in HDs, demonstrating G4 topology formation in the triplex DNA structure, further forming the G4 cavity for DFHO insertion. 24,28,35 In addition, a G4 ligand named 5,10,15,20-tetrakis-(N-methyl-4-pyridyl)porphine (TMPyP4) for competing with DFHO and urea reagent for disrupting G4 cavity were severally adopted in bsFDA. 36,37 As shown in Fig.…”
Section: Mechanism and Optimization For Hds Detection Using Bsfdamentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the inconspicuous G4 topology could be detected in HDs, demonstrating G4 topology formation in the triplex DNA structure, further forming the G4 cavity for DFHO insertion. 24,28,35 In addition, a G4 ligand named 5,10,15,20-tetrakis-(N-methyl-4-pyridyl)porphine (TMPyP4) for competing with DFHO and urea reagent for disrupting G4 cavity were severally adopted in bsFDA. 36,37 As shown in Fig.…”
Section: Mechanism and Optimization For Hds Detection Using Bsfdamentioning
confidence: 99%
“…Currently, optical biosensing assays based on uorescent light-up aptamers (FLAPs) have been regarded as facile, programmable, and label-free detection toolkits for the evaluation of multiple targets and sensing of, for example, metal ions, metabolites, and nucleic acids. [24][25][26][27][28] Among them, the genetically encoded RNA FLAPs such as spinach, broccoli, and corn have been created for specic binding and lighting up the protein chromophore (HBI) derivatives, leading to a robust antiinterference capability and specicity to serve as uorescent protein mimics, which are being applied in cellular imaging. [29][30][31] To further avoid their susceptibility to degradation and reduce the misfolding in RNA FLAPs, the lettuce aptamer, a guanine (G) base-rich DNA sequence, has been selected and optimized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mou et al reported an aptasensor that can detect cancer cells as well as analyze Cu 2+ ions, an important trace element in living cells, by combining the AS1411 aptamer, which can specifically recognize cancer cells, and the Lettuce aptamer, an FLAP that induces the fluorescence of DFHBI-1T [48]. The AS1411 aptamer has a G-quadruplex structure with a G-rich sequence.…”
Section: Fluorescent Light-up Aptamers (Flaps)mentioning
confidence: 99%
“…3,13 For example Lettuce, a DNA FLAP that mimics the fluorescent properties of GFP holds great promise for in pathogen detection or as intracellular sensors for tumor cell recognition. 1416 However, since most DNA aptamer studies focus on their development and characterization in vitro, their potential for applications inside living cells remains largely unexplored. A particular challenge in this context is the difficulty of biosynthesising DNA aptamers in cells.…”
Section: Introductionmentioning
confidence: 99%